Quinine, the richness of Peru’s flora. The construction of a national imaginary from a regional element - Aldana Rivera, Susana (2022)
Quinine and its exploitation during the second half of the 18th century are examples of how national representations and imaginaries are built and rebuilt at a given moment. During this time, quinine became a flagship product in the north of Peru’s viceroyalty, considered a defining element of the Peruvian national coat of arms. In the middle, there were system changes that historically favor independence, supposing the construction of a new type of human relations (modernity) that the republic, the nation, and the nation-state entail. We analyze and outline its demand in the 18th-19th century for what would later become known as a commodity (20th century) and the insertion of social agents in a European international consensus from a market that allows participation in a liberal capitalist system under construction. By 1800, in the locality, the region, the nation, South America, and finally, the international space, situations of economic realization were insinuated in terms of the construction of an international market that became visible over time until reaching the contemporary global apogee.